Man's image in creation narratives - Hannes Olivier (Acta Theologica)
The title of this paper sounds rather unfamiliar, because one usually deals with man as being created in or after the image of God. And that is also the core of biblical anthropology, namely that man is created by God in or according to God's likeness or image. More than anything else the discussion of the meaning of these concepts demut (an abstract noun from dmb - likeness) and, selem (image, statue) have dominated the theological reflection regarding man in te creation narratives.